Curation planning and facilities for asteroid Bennu samples returned by the OSIRIS‐REx mission. (8th April 2023) - Righter, K.; Lunning, N. G.; Nakamura‐Messenger, K.; Snead, C. J.; M Quillan, J.; Calaway, M.; Allums, K.; Rodriguez, M.; Funk, R. C.; Harrington, R. S.; Connelly, W.; Cowden, T.; et al.
Abstract: NASA's OSIRIS‐REx spacecraft collected samples from carbonaceous near‐Earth asteroid (101955) Bennu on October 20, 2020, and will deliver them to the Earth on September 24, 2023. The samples will be processed at the NASA Johnson Space Center (JSC), where most of the sample collection will be subsequently curated in a new cleanroom suite. The spacecraft collected loose regolith two ways: in a bulk sample chamber capable of holding up to 2 kg, and on industrial Velcro "contact pads" intended to collect small particles at the surface. Included in the JSC collection will be the bulk sample, the contact pads, contamination‐monitoring witness plates, and supporting hardware. Planning for the curation of the samples and hardware started at the earliest phase of proposal development and continued in parallel with project development and execution. Because a major mission goal is characterization of organic compounds in the Bennu samples, extra effort was spent in the design stage to ensure a clean curation environment. Here, we describe the preparations to receive the sample, including the design, construction, outfitting, and monitoring of the cleanrooms at JSC; the planned recovery of the sample‐containing capsule when it lands on Earth; and the approach to characterizing and cataloging the samples. These curation efforts will result in the distribution of pristine Bennu samples from JSC to the OSIRIS‐REx science team, international partners, and the global scientific community for years to come.